Transition to a Tube Feeding Formula With Real Food Ingredients in Pediatric Patients With Intestinal Failure. (April 2017) - Samela, Kate; Mokha, Jasmeet; Emerick, Karan; Davidovics, Zev H.
Due to concerns related primarily to allergic response and malabsorption, enteral nutrition therapy has traditionally relied on the use of elemental formulas in children with intestinal failure (IF). Blended food diets via a gastrostomy tube have been reported to improve feeding tolerance in pediatric populations receiving long-term enteral nutrition therapy. Complex macronutrients have been shown to stimulate intestinal adaptation in animal models. We report on our experience in children with IF who had an overall improvement in stool output when transitioned from an elemental formula to a tube feeding formula with real food ingredients (TFRF). Data were collected in a retrospective chart review of children with IF, >1 year of age, who were receiving enteral nutrition via continuous infusion, bolus feeding, or both. Indications for the TFRF trial were diarrhea or inconsistent stooling patterns. Ten children with a mean small bowel length of 48.3 cm were trialed on TFRF. Nine of 10 (90%) children tolerated the transition to 100% TFRF, of which 7 of 9 (78%) had their entire colon in continuity. The average age at successful transition was 29.2 months, and the average length of time to transition to 100% TFRF was 67.3 days. TFRF is well tolerated in children >1 year of age with IF; it also improves their stooling patterns. A commercially available TFRF is a cost-effective and nutritionally adequate means of providing nutrition to this patient population.